FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN FREKUENSI KEJADIAN REGURGITASI PADA BAYI USIA 0-6 BULAN - wati, Dea Septia; Hidayah, Nurul; Supono, Supono (Poltekkes Kemenkes Malang, 2025)
Regurgitation is passage of part the stomach often the main problem with the digestive tract in infants that parents complain when visiting the doctor. The several factors that are rarely known, the prevalence of regurgitation in Indonesia is quite high. This study to explain the determinant factors associated with regurgitation. National and international journals searched through Pubmed, Scient Direct, DOAJ, Research Gate, Google Scholar 2010-2020. After searching according to inclusion, exclusion, and PEOS framework, selected JBI Critical Appraisal tools, 15 journals found that were ready to be analyzed. The results showed that the technique of breastfeeding mothers (3 studies), burping technique (3 studies), and formula feeding (9 studies) the determinant factors associated the frequency of regurgitation in infants aged 0-6 months. The study design contributed cross sectional and quasy experiment showed significant results of analysis and testing. The wrong attachment position when the baby suckles, not burping the baby after feeding, giving formula milk, small baby stomach, baby feels full, and use octopus associated with the frequency of regurgitation in infants. This study can be prevent and treat regurgitation by attachment correct position, burping after feeding, and serving formula milk the right dose